2013
DOI: 10.1080/09588221.2013.818556
|View full text |Cite
|
Sign up to set email alerts
|

Blogs and the development of plurilingual and intercultural competence: report of a co-actional approach in Portuguese foreign language classroom

Abstract: Focusing on the topic of the development of the plurilingual and intercultural competence through the integration of electronic communicative practices both in foreign language classrooms and non-formal contexts, this work aims at defining and characterizing, in view of a co-actional perspective, a "pedagogical blog", by considering it from three different axes: a personal and social dimension, a collaborative and coactional dimension and the management of linguistic and cultural repertoires dimension. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Researchers say that the integration of electronic communicative practices in foreign language classrooms helps learners acquire new knowledge and develops intercultural competences [2], contributes to the development of writing skills and makes information sharing more challenging, meaningful and interesting [3,4,5]. Blogging, as a teaching strategy, provides a motivating learning environment, creates additional opportunities for language learning and furthers learners' independence [6].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers say that the integration of electronic communicative practices in foreign language classrooms helps learners acquire new knowledge and develops intercultural competences [2], contributes to the development of writing skills and makes information sharing more challenging, meaningful and interesting [3,4,5]. Blogging, as a teaching strategy, provides a motivating learning environment, creates additional opportunities for language learning and furthers learners' independence [6].…”
Section: Related Workmentioning
confidence: 99%
“…Although abundant literature exists across many disciplines on the use of social technologies as useful tools for improving communication, collaboration, cultural awareness and information sharing (Aydin 2012;Li and Zhu 2013;Melo-Pfeifer 2013;Vurdien 2013), there is a need for more solid evidence on the potentials, challenges as well as the theoretical grounding of these technologies (Wang and Vasquez 2012;Lantz-Andersson, Vigmo, and Bowen 2013).…”
Section: Objectivesmentioning
confidence: 99%
“…In the last decade, blogs and blogging in English language classroom were empirically investigated from different perspectives, including learners' writing performance (Asoodar, Atai, & Vaezi, 2016;Lee, 2010;Sun, 2010;Vurdien, 2013), learners' reading comprehension (Ducate & Lomicka, 2008;Yakut & Aydin, 2017), learners' oral proficiency (Sun, 2009), learners' autonomous and independent learning (Bhattacharya & Chauhan, 2010;Blackstone, Spiri, & Naganuma, 2007), and learners' intercultural competence (Melo-Pfeifer, 2015). Illuminating the importance of blogs in language learning and teaching, Vurdien (2013) argued that blogs and blogging are extensively explored by the researchers because they can be used for various pedagogical purposes, encourage learners to express their ideas, help teachers ask their learners questions, and provide the opportunity for collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a majority of studies were either qualitative or quantitative. Moreover, Melo-Pfeifer (2015) asserted that the main studies on the use of blogs in language classroom focused on the development of language skills and knowledge in the target language. But there seems to be no relevant literature on the effect of blogs and blogging on language learners' higherorder thinking despite the importance of higher-order thinking skills such as creative and critical thinking skills in learning English.…”
Section: Introductionmentioning
confidence: 99%